Menuju Kebijaksanaan Angkutan Umum Yang Fokus Dan Seimbang Bagi Regulator, Operator Dan Pengguna - Ridwan, Agus Salim (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
Generally, government polia; is defined to protect public transport operators and to determinateoperator business which can reach sustainable of business public transport, equity and efficiena;.Sustainable impliazte operator fur reuenue accepted which am cmier their expenditure, so operatorscan protect their wlwle aperationnl S1JSfems. EqHihJ relnti: to cnpabilihJ and distnbution of peopleincome, so that fare can be reached m; all level income of people, whereas efficiena; can contribute toeconomical efficiena;.With multicriteria analysis and cause-effect analysis (jishbone) approaches to senrice qualitt;, affectivitiesof business SlJStem and gcmernment regulntion can focus on polietJ system and optimal SlJSfemrelated to goal which can be reached. Tiie analysis can result comprehensizie poliCIJ and clarity objectives.Polia; instruments consist of fare, route regulntion, testing, licensing and other instrumentsthat will be arranged such as demand, supply, market stnicture and etc. Finally performance resultedfrom this poliClj prmride more priorihJ lu;pped bij gmiernment, operators and users.The result of the study in Indonesia is obtained that poliCIJ implementation should be distinguishedpublic transport operator betmxn inter cities and within cihJ. 171us for public transport condition andpolia; needed slwuld different such as highway, railwm;, seaport and air transport.Key word: instnmien ts, goo! and perfomumce policies